Distribución espacial del sector servicios en la Ciudad de México, 1960-2008 - Garza, Gustavo (El Colegio de México A.C., 2012)
This paper’s proposal is to analyze the evolution of the spatial conformation of the service sector within the Metropolitan Area of Mexico City from 1960 to 2008. The document, divided in five major sections, studies the gross domestic product distribution of the commercial and service activities located in five areas in which the metropolis is subdivided. Three indicators are calculated to measure and analyze the evolution of the location of tertiary activities in each stage of the expansion of the city. In its most general formulation, it is concluded that the central node increases its index of relative concentration throughout the period, gives the city a spatial classical tertiary organization of activities, that is, a significant downward trend from the center to the periphery.